2019
DOI: 10.1101/846816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synapse type-specific proteomic dissection identifies IgSF8 as a hippocampal CA3 microcircuit organizer

Abstract: Synaptic diversity is a key feature of neural circuits. Its underlying molecular basis is largely unknown, due to the challenge of analyzing the protein composition of specific synapse types.Here, we isolate the hippocampal mossy fiber (MF) synapse, taking advantage of its unique size and architecture, and dissect its proteome. We identify a rich cell-surface repertoire that includes 5 adhesion proteins, guidance cue receptors, extracellular matrix (ECM) proteins, and proteins of unknown function. Among the la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 116 publications
1
22
0
Order By: Relevance
“…Future developments will allow a more thorough multi-omics (Hafner et al, 2019;Poulopoulos et al, 2019) analysis of dopaminergic samples prone to unravelling important key molecular signatures of dopamine hub synapses. More generally, results from our study and the work of Apostolo and colleagues (Apóstolo et al, 2019) on mossy fibre terminals of the hippocampus show that FASS synaptomics is a powerful tool for the exploration of projection-specific synaptomes (Grant, 2019;Zhu et al, 2018).…”
Section: Synaptic Adhesion At Dopaminergic Synaptic Hubssupporting
confidence: 62%
“…Future developments will allow a more thorough multi-omics (Hafner et al, 2019;Poulopoulos et al, 2019) analysis of dopaminergic samples prone to unravelling important key molecular signatures of dopamine hub synapses. More generally, results from our study and the work of Apostolo and colleagues (Apóstolo et al, 2019) on mossy fibre terminals of the hippocampus show that FASS synaptomics is a powerful tool for the exploration of projection-specific synaptomes (Grant, 2019;Zhu et al, 2018).…”
Section: Synaptic Adhesion At Dopaminergic Synaptic Hubssupporting
confidence: 62%
“…To understand if Lphn2 is topographically downregulated, CA1 SLM was microdissected from Pde1c-Cre -/- ;DTA and Pde1c-Cre +/- ;DTA groups at P15 and P30. Total RNA was extracted from the tissue and qRT-PCR analysis was performed targeting genes specific for CA1 synapses ( Lphn2 , (Donohue et al, 2021) Robo2 (Blockus et al, 2021) or CA3 synapses ( Igsf8, Neo1 (Apóstolo et al, 2020)) to assess specificity of changes (Figure 4A). qRT-PCR analysis revealed that Lphn2 and Robo2 were both significantly upregulated at P15 Pde1c-Cre +/- ;DTA compared to Pde1c-Cre -/- ;DTA and conversely, were significantly downregulated at P30 Pde1c-Cre -/- ;DTA compared to Pde1c-Cre -/- ;DTA (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Profiling the axonal proteome or transcriptome is challenging, particularly from complex tissues composed of multiple intermingled cell types. Canonical approaches utilize cell culture models in compartmentalized devices to ensure directional growth (Cagnetta et al, 2018; Chuang et al, 2018), laser capture microdissection of axon terminals (Zivraj et al, 2010), manual dissection of nerve segments (Michaelevski et al, 2010), synaptosome sorting from hippocampal mossy fibers (Apóstolo et al, 2020), or growth cone (GC) sorting from developing brain (Chauhan et al, 2020; Poulopoulos et al, 2019). However, no single approach can flexibly measure the overall axonal proteome across a wide age range, with high efficiency, genetic targeting, and pre-synaptic specificity.…”
Section: Discussionmentioning
confidence: 99%